THE PROFILE OF SUPEROXIDA DISMUTASE AND MALONDIALDEYDE LEVEL IN THE LIVER TISSUE OF HYPERCHOLESTEROLEMIC RATS TREATED WITH Holothuria nobilis POLYSACCHARIDE - Ulhusna, Fitrah Asma; Winarto, Adi; Wresdiyati, Tutik (Universitas Syiah Kuala, 2019)
The aim of this research was to analyze the profile of superoxide dismutase (SOD) and malondialdehyde (MDA) on the liver tissue of hypercholesterolemic rats which were given Holothuria nobilis polysaccharides (HNP). A total of 15 male rats strain Sprague Dawley were divided into prevention and curative groups. Prevention group consisted of negative/non-hypercholesterolemic group (K-), positive/hypercholesterolemic group (K+), and hypercholesterolemic prevention group which were given 1% cholesterol diet and HNP at dose of 400 mg/kg bw (PCh). The treatments were given for 28 days. The curative group was consisted of the hypercholesterolemic group, which was given 1% cholesterol diet for 28 days, then followed by standard diet for 28 days (Ch), and the hypercholesterolemia curative group which was given 1% cholesterol diet for 28 days, then followed by 400 mg/kg bw HNP for 28 days (ChP). The antioxidant activity of HNP was analyzed by DPPH method. At the end of study the liver tissue was collected and analyzed for MDA, SOD while Cu,Zn-SOD was analyzed by immunohistochemical technique. The results showed that the antioxidant activity of HNP was weak. The MDA level (g/g) in K-, K+, PCh, Ch, and ChP groups were 1.190.6; 3.370.79; 0.290.14; 9.110.72; and 3.141.06, respectively. The SOD activities (U/g) in K-, K+, PCh, Ch, and ChP groups were 2141.1183.88; 1541211.69; 2096.67166.66; 1063.3388.19; 1685.55167.77, respectively. The immuno reactivity of Cu,Zn-SOD showed that HNP could increase Cu,Zn-SOD in the liver tissues of both groups. This study concluded that the HNP increased SOD activity, Cu,Zn-SOD antioxidant content, and decreased MDA levels in the liver tissues of hypercholesterolemic rats in both preventive and curative groups.